PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGRI 005 RAJA BEJAMU KECAMATAN SINABOI Dewi Marlina, - Dewi Marlina; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study is based on the low learning outcomes of IPS students of grade IV SDN 005 King Bejamu Sinaboi District Academic Year 2016/2017. From the data, it is known that from 25 students, the KKM is determined by the school 70. The number of students who reach the KKM score is only 3 people (12%) and the number of students who have not reached the KKM score is 22 people (88%), with the average class 62.8. This research is a classroom action research conducted collaboratively and participatively in collaboration with fourth grade IPS teacher SDN 005 Raja Bejamu Kecamatan Sinaboi. The instrument of this study consists of learning devices used in this study based on Education Unit Level Curriculum (KTSP). Learning tools consist of syllabus, lesson plans, student worksheets and observation sheets. The results obtained by teacher activity On siklu II meeting 1 is 79.17 with good category and second meeting second cycle is 91,67 with very good category. Then the percentage of first cycle activity of the first student is 54,17 with enough category, at the second meeting of cycle I that is 70,833 with good category. In the second cycle of meeting I is 83.33 with good category, and meeting II is 87,5 with very good category. As for the result of student learning that complete before held action only 3 student (12%) with average value 62,8. In the daily test I cycle I the number of completed students increased to 12 students or (12%) with an average score of 67.6. Furthermore, in II repetition cycle II increased again with the total number of completed students as much as 22 students or (88%) with an average score of 83.6. The increase that occurred on student learning outcomes between the basic score of the one cycle with an average of 7.68 and between the basic score of the second cycle with an average of 33.12. This means that the classical value obtained by students has been above the established KKM.Keywords: Inquiry Model, Learning Outcomes IPS